2013
DOI: 10.1088/0967-3334/34/12/1657
|View full text |Cite
|
Sign up to set email alerts
|

Effects of elastase and collagenase on the nonlinearity and anisotropy of porcine aorta

Abstract: We use enzymatic manipulation methods to investigate the individual and combined roles of elastin and collagen on arterial mechanics. Porcine aortic tissues were treated for differing amounts of time using enzymes elastase and collagenase to cause degradation in substrate proteins elastin and collagen and obtain variable tissue architecture. We use equibiaxial mechanical tests to quantify the material properties of control and enzyme treated tissues and histological methods to visualize the underlying tissue m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
23
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 33 publications
6
23
1
Order By: Relevance
“…Dobrin and coworkers found that there was no change in axial compliance with collagenase treatment, contradicting the results of this study [49,50]. However Gundiah et al found collagenase treatment affected wall compliance in both directions, which supports the findings here [18]. The differences in behaviour in this study are most pronounced in the axial direction, with both the fracture stress and stretch being significantly different, whilst only the stretch is significantly different in the circumferential direction.…”
Section: Collagenase Treatmentcontrasting
confidence: 90%
See 4 more Smart Citations
“…Dobrin and coworkers found that there was no change in axial compliance with collagenase treatment, contradicting the results of this study [49,50]. However Gundiah et al found collagenase treatment affected wall compliance in both directions, which supports the findings here [18]. The differences in behaviour in this study are most pronounced in the axial direction, with both the fracture stress and stretch being significantly different, whilst only the stretch is significantly different in the circumferential direction.…”
Section: Collagenase Treatmentcontrasting
confidence: 90%
“…Their tensile test data, correspondingly, showed increased stiffness in diseased tissue and curves shifted towards lower strains. This behaviour coincides with results reported in Gundiah et al when elastin was artificially degraded [18]. However, it was not reflected in our results, wherein curves for elastase treated samples showed a shift towards higher strains.…”
Section: Diseased Tissue Comparisonsupporting
confidence: 89%
See 3 more Smart Citations